Answer

Verified

339.3k+ views

**Hint:**To find the three numbers that are in arithmetic progression, we take the number progression terms as \[a-d,a,a+d\] first we will form an equation where we add these three numbers and equate it with the sum of the three numbers i.e. \[3\] and after this we will find the product of the three terms and then equate it with \[-35\].

For Sum: \[\left( a-d \right)+a+\left( a+d \right)=3\]

For Product: \[\left( a-d \right)\times a\times \left( a+d \right)=-35\]

As \[a\] is the first term and \[d\] is the difference value in each A.P.

**Complete step by step solution:**

According to the question given, we can say that the sum of the three numbers of an arithmetic progression is \[3\] and the product of these three numbers are given as \[-35\].

Now write the progression in terms of the first term and the middle term as \[a\] is the first term and \[d\] is the difference in each term. We get the value of progression as:

\[\Rightarrow a-d,a,a+d\]

After this we add the three numbers and make it equal to \[3\] as given below:

\[\Rightarrow \left( a-d \right)+a+\left( a+d \right)=3\]

\[\Rightarrow a+a+a=3\]

\[\Rightarrow a=1\]

Similarly, as we have added the numbers of the arithmetic progression we will multiply the same and equate it with the value of \[-35\] as given below:

\[\Rightarrow \left( a-d \right)\times a\times \left( a+d \right)=-35\]

Placing the value of \[a=1\], we get the value of \[d\] as:

\[\Rightarrow 1-d\times 1\times 1+d=-35\]

\[\Rightarrow {{1}^{2}}-{{d}^{2}}=-35\]

Changing the negative sign by interchanging the values from LHS to RHS as:

\[\Rightarrow {{d}^{2}}=36\]

\[\Rightarrow d=\pm 6\]

Now that we have got the numbers or the value of the first and the last term, we can place those values in the arithmetic terms \[a-d,a,a+d\], we can get the value of the three numbers:

The value of the first number is given as:

\[\Rightarrow a-d\]

Placing the values in the above term for \[a=1\] and \[d=6\] (we can take either \[6\] or \[-6\]), we get:

\[\Rightarrow 1-6\]

\[\Rightarrow -5\]

The value of the first number is given as:

\[\Rightarrow a\]

Placing the values in the above term for \[a=1\] and \[d=6\] (we can take either \[6\] or \[-6\]), we get:

\[\Rightarrow 1\]

The value of the first number is given as:

\[\Rightarrow a+d\]

Placing the values in the above term for \[a=1\] and \[d=6\] (we can take either \[6\] or \[-6\]), we get:

\[\Rightarrow 1+6\]

\[\Rightarrow 7\]

**Therefore, the numbers that are given in arithmetic progression are given as: \[-5,1,7\].**

**Note:**Arithmetic progression is a method in which the sequence follows a constant difference pattern amongst the consecutive terms given. The formula for the nth term of a sequence is given as \[{{a}_{n}}={{a}_{1}}+\left( n-1 \right)d,n=1,2,3....\]

Recently Updated Pages

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

How do you arrange NH4 + BF3 H2O C2H2 in increasing class 11 chemistry CBSE

Is H mCT and q mCT the same thing If so which is more class 11 chemistry CBSE

What are the possible quantum number for the last outermost class 11 chemistry CBSE

Is C2 paramagnetic or diamagnetic class 11 chemistry CBSE

What happens when entropy reaches maximum class 11 chemistry JEE_Main

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Describe the poetic devices used in the poem Aunt Jennifers class 12 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Change the following sentences into negative and interrogative class 10 english CBSE

State the laws of reflection of light

State and prove Bernoullis theorem class 11 physics CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE